Efficacy of repetitive transcranial stimulation with H-coil for treatment of intractable neuropathic pain in lower extremities. Issue 3 (March 2016) - Shimizu, T.; Maruo, T.; Hosomi, K.; Goto, Y.; Yokoe, M.; Kageyama, Y.; Yanagisawa, T.; Oshino, S.; Kishima, H.; Yoshimine, T.; Saitoh, Y.
Abstract : Objectives: In our previous study, repetitive transcranial magnetic stimulation (rTMS) using figure-8 shaped coil could relieve neuropathic pain (NP) less effectively in the lower extremities than the upper ones. It may be because the primary cortex (M1) of lower extremities locate in the deeper regions. H-coil is a novel development that can stimulate deep neuronal regions effectively. In this study, we compared the clinical effects for NP patients in their lower extremities between rTMS with H-coil, rTMS with figure-8 shaped coil and sham stimulation. Methods: This was a randomized, double-blind, three-way crossover trial. 17 NP patients in their lower extremities received three types of stimulations for 5 consecutive days with 17 days follow-up. In each rTMS session, 5-Hz rTMS to M1 corresponding to the painful lower extremity was administered. Outcome measures were visual analogue scale (VAS). Results: H-coil rTMS, compared with the sham and figure-8 coil, showed significant pain improvement soon and one hour after rTMS in VAS ( p < .001). No serious adverse events were observed. Carry-over effects were not seen at the last day of follow-up. Conclusions & key message: Our findings demonstrated that rTMS with H-coil could be tolerable and provide good pain relief in NP patients in their lower extremities.